Optimalisasi Keuntungan Usaha Mikro Melalui Penerapan Sistem Biaya Produksi yang Tepat dan Akurat - Akmal, Oktafiana; Shara, Yuni; Syahrizal, Muhammad (Forum Kerjasama Pendidikan Tinggi, 2025)
This community service activity was carried out to address the problem of weak financial management and inaccurate production cost calculation among micro-entrepreneurs, particularly tofu producers in Kampung Tahu Binjai, Binjai City, North Sumatra. Most business owners lacked structured cost recording systems, causing product pricing to rely on intuition rather than accurate cost analysis. Such conditions resulted in operational inefficiencies and reduced profit margins. The main objective of this activity was to strengthen the financial literacy and managerial capacity of MSME actors through integrated training, which included cost of goods manufactured (COGM) calculation using the full costing method, preparation of simple income statements, and the adoption of digital financial recordkeeping. The approach consisted of initial observation, practice-based training, intensive mentoring, and post-activity evaluation to ensure behavioral change and real implementation in the field. A total of 20 tofu producers participated in this program, most of whom had basic educational backgrounds and had never implemented formal accounting systems. The evaluation showed a significant increase in participants’ understanding of fixed and variable costs, COGM computation, and financial reporting. The level of understanding rose from 10% before training to 85–90% afterward, with a participant satisfaction rate of 90%. Moreover, most participants began using simple digital bookkeeping based on spreadsheet applications. Beyond technical skills, this program also fostered awareness of financial discipline, the separation between personal and business finances, and the strategic use of financial statements for decision-making and credit access. The results demonstrate that a literacy-based, practice-oriented, and digitally supported training model can improve the efficiency, transparency, and profitability of microenterprises. This approach can be replicated as a community-based MSME empowerment model to promote sustainable local economic growth and strengthen financial resilience among small-scale food producers in Indonesia.